Cecropins, antibacterial peptides from insects and mammals, are potently fungicidal against Candida albicans - Jörg Andrä; Otto Berninghausen; Matthias Leippe (Medical microbiology and immunology, 2001)
Natural products are the major source of lead compounds for drugs against human pathogens. Among the first natural peptides from animals for which a potent antibacterial activity has been recognized were the cecropins. The 30- to 40-residue α-helical peptides display their activity by permeabilizing the membranes of bacteria. Although originally isolated from insect hemolymph, a structural and functional correlate was also found in a mammal. Here, we report on the finding that cecropin A and B from the silk moth Cecropia as well as the porcine cecropin P1 are capable of inhibiting the growth of and to kill yeast-phase Candida albicans. The peptides were tested in radial diffusion and microbroth dilution assays. They displayed potent activity against a clinical isolate as well as against defined culture strains of the pathogenic yeast but are of exceedingly low cytotoxicity towards the human cell line Jurkat. The candidacidal properties of the intensely studied molecules known to be highly active against Gram-positive and Gram-negative bacteria may renew the interest in these natural broad-spectrum peptide antibiotics and their limited cytotoxicity to human cells may be exploited for the development of topical therapeutics against pathogens resistant to classical antibiotics.
Keywords: Antimicrobial peptides; Candida albicans; Cecropins; Peptide antibiotics